Improvements in no evidence of disease activity with ublituximab vs. teriflunomide in the ULTIMATE phase 3 studies in relapsing multiple sclerosis - Alvarez, Enrique; Steinman, Lawrence; Fox, Edward J.; Hartung, Hans-Peter; Qian, Peiqing; Wray, Sibyl; Robertson, Derrick; Selmaj, Krzysztof; Wynn, Daniel; Mok, Koby; Xu, Yihuan; Bodhinathan, Karthik; et al. (Frontiers in Neurology, 2024)
Background Ublituximab is a novel anti-CD20 monoclonal antibody glycoengineered for enhanced antibody-dependent cellular cytotoxicity. The phase 3 ULTIMATE I and II studies showed significant improvements in annualized relapse rate, total number of gadolinium-enhancing (Gd+) T1 lesions, and total number of new or enlarging T2 at Week 96, as well as improvement in the proportion of participants with no evidence of disease activity (NEDA) from Weeks 24–96 with ublituximab vs. teriflunomide. Methods In ULTIMATE I (NCT03277261; www.clinicaltrials.gov) (N = 549) and II (NCT03277248; www.clinicaltrials.gov) (N = 545), participants with relapsing multiple sclerosis received ublituximab 450 mg intravenous infusion every 24 weeks (following Day 1 infusion of 150 mg and Day 15 infusion of 450 mg) or teriflunomide 14 mg oral once daily for 96 weeks. Pooled post hoc analyses evaluated NEDA by treatment epoch and participant subtype: age ( ≤ 38 or >38 years), early or later disease (<3 or ≥3 years following diagnosis), treatment history (treatment naïve or previously treated), 0 or ≥1 Gd+ T1 lesions at baseline, and Expanded Disability Status Scale score ≤ 3.5 or >3.5 at baseline. NEDA was defined as no confirmed relapses, no Gd+ T1 lesions, no new or enlarging T2 lesions, and no disability progression confirmed for ≥12 weeks. Results NEDA rates in the ublituximab vs. teriflunomide cohorts by treatment epoch were: Weeks 0–96, 44.6% vs. 12.4% (3.6 × improvement); Weeks 24–96 (re-baselined), 82.1% vs. 22.5% (3.6 × improvement); and Weeks 48–96 (re-baselined), 88.2% vs. 30.4% (2.9 × improvement) (all p < 0.0001). The primary driver of disease activity in ublituximab-treated participants was new or enlarging T2 lesions during Weeks 0–24. 41.8% of ublituximab-treated participants who had evidence of disease activity in the first year (Weeks 0–48) experienced NEDA in the second year of treatment (Weeks 48–96) compared with 17.3% of teriflunomide-treated participants. At Weeks 24–96 (re-baselined), rates of NEDA were significantly higher with ublituximab than teriflunomide in all participant subtypes (all p < 0.0001). Conclusions ULTIMATE I and II pooled post hoc analyses demonstrated a consistent NEDA benefit among ublituximab-treated participants across treatment epochs and key participant subpopulations.